The rolling resistances of roller skis and their effects on human performance during treadmill roller skiing - Ainegren, M. (2010)
Modern ski-treadmills allow cross-country skiers, biathletes and ski-orienteers to test their physical performance in a laboratory environment using classical and freestyle techniques on roller skis. For elite athletes the differences in performance between test occasions are quite small, thus emphasising the importance of knowing the roller skis` rolling resistance coefficient, µR, in order to allow correct comparisons between the results, as well as providing the opportunity to study work economy between different athletes, test occasions and core techniques.